2019
DOI: 10.1186/s13068-019-1498-4
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics of the Hu sheep rumen microbiome reveals novel cellulases

Abstract: Background Cellulosic biomass has great potential as a renewable biofuel resource. Robust, high-performance enzymes are needed to effectively utilize this valuable resource. In this study, metatranscriptomics was used to explore the carbohydrate-active enzymes (CAZymes), especially glycoside hydrolases (GHs), present in the rumen microbiome of Hu sheep. Select CAZymes were experimentally verified and characterized after cloning and expression in E. coli . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The N50 of our metatranscriptome assembly was ~ 700 nt, which is congruent to the expected length of Prokaryotic mRNA molecules, (~ 900 pb long). Additionally, > 54% of the total reads from our samples mapped back to the assembly, suggesting an adequate assembly, even better than the ones obtained in other studies using a similar methodology [45]. Indeed, when we remapped sequencing data from different cohorts, we recovered ~ 25% of the reads despite them being of healthy adults from different populations, so this metatranscriptome and Secrebiome could be considered as a reference for further studies in different populations.…”
Section: Discussionmentioning
confidence: 55%
“…The N50 of our metatranscriptome assembly was ~ 700 nt, which is congruent to the expected length of Prokaryotic mRNA molecules, (~ 900 pb long). Additionally, > 54% of the total reads from our samples mapped back to the assembly, suggesting an adequate assembly, even better than the ones obtained in other studies using a similar methodology [45]. Indeed, when we remapped sequencing data from different cohorts, we recovered ~ 25% of the reads despite them being of healthy adults from different populations, so this metatranscriptome and Secrebiome could be considered as a reference for further studies in different populations.…”
Section: Discussionmentioning
confidence: 55%
“…The application of omics technologies reveals more and more cellulolytic bacteria. Studies using metatranscriptomics found that the rumen microbiome in Hu sheep (a local breed in China) encoded a repertoire of new cellulases ( He et al., 2019 ). Cellulases enable the utilization of low-quality roughage (e.g., corn stover) and can be used to digest roughage for ruminants.…”
Section: Importance Of the Rumen Microbiotamentioning
confidence: 99%
“…In addition, animals can use some biomass that cannot be used by humans, which can effectively solve the problem of competition for food between humans and livestock. For example, ruminants can utilize plant cell wall biomass ( Dai et al., 2015 ; He et al., 2019 ), many by-products of agriculture and food industry as feed owing to the rumen microbiota ( Kimball, 1991 ; Westendorf, 2000 ; Malaweera and Wijesundara, 2014 ). It has been suggested that ruminant livestock farming has the potential to minimize the use of human-edible grains by utilizing available forage resources within a given system ( Eisler et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It led to breakthrough of the first exo-1,4-β-xylanase (act on xylo-oligomers) from family 11 of glycoside hydrolase (GH11) [ 54 ]. Using approaches of RT-PCR, the microbial origin and expression level of cellulase gene was examined in the rumen of Hu sheep [ 55 ]. Metatranscriptomic analysis of rumen microorganisms of adult Holstein cows indicated high quality of non-rRNA reads and the transcripts encoding GHs and some carbohydrate binding molecules [ 56 ].…”
Section: Omics Based Approaches Aimed At Prospection For Improved Cazmentioning
confidence: 99%
“…These techniques have already showed their efficiency by being able to discover various new non culturable bacteria possessing polysaccharide degrading abilities [ [195] , [196] , [197] ] as well as novel CAZymes [ 55 , 198 , 199 ] with various roles in polysaccharides degradation abilities which would not have been possible with the classical culture-based methods [ 200 ]. Metagenomic study of rumen of Mehsani buffalo and Korean black goat rumen unearthed novel GH26 and KG51 genes respectively which were than expressed and characterized [ 201 , 202 ].…”
Section: Cazyme Application In Biorefineriesmentioning
confidence: 99%